Estudo de propriedades mecânicas de concretos produzidos com diferentes agregados reciclados - Silva, Karlisson André Nunes da (2011)
The research aimed to evaluate the mechanical properties of concrete produced with recycled coarse aggregate, at ages 28 days and 240 days for use in structural elements. We used two types of waste: a mixture of waste consisting of construction, renovation and demolition waste and others just concrete. The first was collected on the campus of Federal University of Alagoas, the second was from research papers and several samples of concrete works of Macedonia and other cities in the state. After the processing of waste, only the coarse aggregate were used. For the production of concrete were considered two ratios a / c (0.4 and 0.5) and two levels of substitution of coarse aggregate (100% RCD and 100% Concrete). The implementation of these combinations were defined using 22 factorial design for the age of 28 days. The properties studied were compressive strength and modulus of elasticity. From the results obtained by statistical analysis to the age of 28 days was observed that the compressive strength of concrete obeyed the Law of Abrams and the w / c ratio had a significant effect on this property. As for the modulus of elasticity specifies the mass had a greater influence on its outcome. With regard to older concrete mechanical properties mentioned above had a satisfactory outcome when compared to reference concrete. The results show that the use of concrete with coarse aggregate of both types may be viable for certain class of concrete strength.